2018
DOI: 10.3892/ijmm.2018.3632
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑125 inhibits RKO colorectal cancer cell growth by targeting VEGF

Abstract: Colorectal cancer (CRC) is one of the major types of cancer and causes of mortality worldwide, and it remains the third most common cause of cancer‑associated mortality worldwide. MicroRNAs (miRNAs) are a class of small RNAs, which have been shown to be associated with CRC. In the present study, an MTT assay and proliferating cell nuclear antigen (PCNA) protein examination assay were performed to detect RKO cell viability. Hoechst staining, and caspase‑3 activity and BrdU incorporation assays were performed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…In laryngeal cancer, Zhang et al (52) demonstrated that downregulated miR-206 promoted the proliferation and invasion of cancer cells by modulating VEGF expression. Wu et al (53) suggested that miR-125 suppressed cell growth of RKO colorectal cancer cells via targeting VEGF. It was reported that the EMT process is involved in the migration and invasion of cancer cells and plays a critical role in cancer metastasis (54,55).…”
Section: Discussionmentioning
confidence: 99%
“…In laryngeal cancer, Zhang et al (52) demonstrated that downregulated miR-206 promoted the proliferation and invasion of cancer cells by modulating VEGF expression. Wu et al (53) suggested that miR-125 suppressed cell growth of RKO colorectal cancer cells via targeting VEGF. It was reported that the EMT process is involved in the migration and invasion of cancer cells and plays a critical role in cancer metastasis (54,55).…”
Section: Discussionmentioning
confidence: 99%
“…Cell cycle and apoptosis were analyzed by using flow cytometry, of which the protocol was reported in the literature ( 31 33 ). For the cell cycle, around 1 × 10 6 cells were washed by cold PBS and fixed in 70% ethanol at −20°C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have revealed that miRNA polymorphisms can affect the levels of VEGF and VEGFRs, such as KDR, leading to the inhibition of the VEGF pathway and abnormal angiogenesis [6,34,35]. In particular, understanding the mechanisms underlying the miRNA-mediated regulation of the VEGF-VEGFR pathway during pregnancy and fetal development is critical, as angiogenesis plays key roles in establishing and maintaining pregnancy [31,36].…”
Section: Discussionmentioning
confidence: 99%